Fungal and bacterial communities of ‘Pinot noir’ must: effects of vintage, growing region, climate, and basic must chemistry - Kerri L. Steenwerth; Ian Morelan; Ruby Stahel; Rosa Figueroa-Balderas; Dario Cantu; Jungmin Lee; Ron C. Runnebaum; Amisha T. Poret-Peterson (PeerJ, 2021)
Background The geographic and temporal distributions of bacterial and fungal populations are poorly understood within the same wine grape cultivar. In this work, we describe the microbial composition from ‘Pinot noir’ must with respect to vintage, growing region, climate, and must chemistry across the states of California and Oregon, USA. Materials and Methods We sampled ‘Pinot noir’ clone 667 clusters from 15 vineyards existing in a latitudinal gradient spanning nearly 1,200 km in California and Oregon for two vintages (2016 and 2017). Regions included five American Viticultural Areas (AVA). In order from southern California to Oregon, these AVAs were Santa Barbara, Monterey, Sonoma, Mendocino, and Willamette Valley. Uninoculated grape musts were subjected to 16S rRNA gene and ITS-1 amplicon sequencing to assess composition of microbial communities. We also measured grape maturity metrics. Finally, to describe regions by precipitation and growing degree days, we queried the Parameter-elevation Regressions on Independent Slopes Model (PRISM) spatial climate dataset. Results Most of the dominant bacterial taxa in must samples were in the family Enterobacteriaceae, notably the lactic acid bacteria or the acetic acid bacteria groups, but some, like the betaproteobacterial genus Massilia, belonged to groups not commonly found in grape musts. Fungal communities were dominated by Hanseniaspora uvarum (Saccharomycetaceae). We detected relationships between covariates (e.g., vintage, precipitation during the growing season, pH, titratable acidity, and total soluble solids) and bacterial genera Gluconobacter and Tatumella in the family Enterobacteraceae, Sphingomonas (Sphingomonodaceae), Lactobacillus (Lactobacillaceae), and Massilia (Oxalobacteraceae), as well as fungal genera in Hanseniaspora, Kazachstania, Lachancea, Torulaspora in the family Saccharomycetaceae, as well as Alternaria (Pleosporaceae), Erysiphe (Erysiphaceae), and Udeniomyces (Cystofilobasidiaceae). Fungal community distances were significantly correlated with geographic distances, but this was not observed for bacterial communities. Climate varied across regions and vintages, with growing season precipitation ranging from 11 mm to 285 mm and growing degree days ranging from 1,245 to 1,846. Discussion We determined that (1) bacterial beta diversity is structured by growing season precipitation, (2) fungal beta diversity reflects growing season precipitation and growing degree days, and (3) microbial differential abundances of specific genera vary with vintage, growing season precipitation, and fruit maturity metrics. Further, the correlation between fungal community dissimilarities and geographic distance suggests dispersal limitation and the vineyard as a source for abundant fungal taxa. Contrasting this observation, the lack of correlation between bacterial community dissimilarity and geographic distance suggests that environmental filtering is shaping these communities.